Cetoacidosis diabética en paciente de sexo femenino de 18 años de edad - Vaca Escobar, Juleidy Ariana (2019)
Diabetes is a chronic disease and appears when the pancreas does not produce enough insulin or when the body does not use it effectively, in the development of diabetes genetic and environmental factors are related, It is a disease with rapid growth. Globally, according to reports from the World Health Organization, the number has increased from 108 million in 1980 to 422 million in 2014. The case of an 18-year-old female patient with a personal pathological history of DMI is presented, she says that during the last weeks she began to present polydipsia, polyuria and dysuria, and in the last days she presented asthenia, later drowsiness and hours later to emergency with state of alteration of consciousness. Through the clinical, pathological and anthropometric correlation, the diagnosis of diabetic and overweight ketoacidosis was reached, which developed a nutritional plan appropriate to the diagnosis of the patient, to provide the necessary instruments to achieve the best possible control of glycemia, lipidemia and blood pressure, in order to prevent, delay or stop microvascular and macrovascular complications. The case is presented below with a nutritional intervention: a diet of 1707.5 kcal / day - hypocarbon, hypocaloric, normoproteic with a distribution of macronutrients: 60% carbohydrates, 15% protein and 25% fats and a fractionation of 3 main meals and 2 refreshments